The expectations of patients with psychical disorders towards their family and medical staff - Kłak, Marta (Current Problems of Psychiatry, 2013)
The aim of the paper was to present the most important expectations of patients with psychical disorders towards their family and medical staff. Patients with mental disorders staying at mental institutions expect their medical staff to be professional, competent, understanding, willing to talk, taking interest in their life problems as well as those resulting from prolonged hospital stay. They need devotion and psychological support. Additionally patients seek information about the state of their health, used medicines and other aspects of their hospital life: how to deal with their condition, how to cope with difficulties and how to manage with stressful situations. The attitude of hospital personnel towards the mental patients should be characterized by infinite patience, kindness, politeness, warmth and care. The sick also wait for a nice and quiet temper, smile, as much as respect and appropriate treatment. Such qualities in contact with patients give them a sense of security and inspire their confidence, which allows patients to open up. In a safe atmosphere, it is easier for them to talk about private feelings and intimate problems caused by the illness. From the family members, to whom their relatives’ illness often comes as a shock and makes them feel ashamed, patients expect absolute understanding, support, acceptance and love.